Disaster Relief and Preparedness: Enhancing Supply Chain Management system to support effective flood relief operation. - Husain, Wahidah (Universiti Sains Malaysia, 2016)
Insufficient coordination of supply and demand management during flood disaster can hold back the process of goods delivery to the flood victims at the right time, in the right amount and at the right location. Poor matching of the supply and demand can cause delay in decision making process in resolving immediate needs during critical situation.